Chamunda stands atop a human form flanked by two attendants - Temples of India Project Team (Jio Institute, 2024)
Chamunda stands atop a human form, flanked by two attendants and an animal companion. Though many of her arms are fragmented, her divine attributes are evident. In her upper hands, she carries a sarpa (snake). Her intact right arms carry a damru (drum) and a trishula (trident), while her left hands cradle a khatvanga (staff with a human skull) and a bowl, with the finger of her left hand touching her lips. Chamunda’s portrayal emphasizes her skeletal form, with a cavity in her belly housing a scorpion, symbolizing transformative power. Her lower body is draped modestly with a loin cloth. Adjacent to her, a seated figure grasps a bowl from which he is drinking. It is speculated that one of the Goddess’s broken hands may have held a munda (severed human head). The presence of the seated figure suggests the consumption of the blood dripping from the severed head.